On the Possibility of Extending the European Green Belt to the Hungarian-Romanian Border Region - Zoltán Zakota; Tamás Z Zakota (Fábos Conference on Landscape and Greenway Planning, 2016)
In our present paper we make an attempt to put together some relevant information, based mainly on regional statistics and administrative data, in order to outline a blueprint of a greenway plan for the Hungarian-Romanian border area that could be able to create more opportunities for the sustainable development of the region through the green belt development. The target-area consists of eight counties, four on each side of the common border: Szabolcs- Szatmár-Bereg, Hajdú-Bihar, Békés and Csongrád in Hungary, respectively Satu Mare, Bihor, Arad and Timiș in Romania. Protection of nature and, in general, environment is an important issue because there are 235 ha of protected natural areas (natural parks and landscape protected areas) in the region representing 4.7% of its total territory (Final Evaluation Report). Our main purpose is to identify potential factors that could positively contribute to establishing a green belt in this area, such as: usage of agricultural terrains, existing experience in the environmental domain, as well as the potential effects of establishing a green belt in the border area.
Keywords: greenways; green belt; hungary; romania; extension; europe